2018
DOI: 10.20471/acc.2018.57.02.09
|View full text |Cite
|
Sign up to set email alerts
|

ALBI Score as a Predictor of Survival in Patients with Compensated Cirrhosis Resected for Hepatocellular Carcinoma: Exploratory Evaluation in Relationship to PALBI and MELD Liver Function Scores

Abstract: SUMMARY – The aim of the study was to explore predictive value of the ALBI, PALBI and MELD scores on survival in patients resected for hepatocellular carcinoma with compensated liver cirrhosis and no macrovascular infiltration. In this retrospective study, longitudinal survival analysis was performed. We analyzed patient/tumor characteristics and MELD, ALBI and PALBI scores as liver function tests for predicting survival outcome. Survival was analyzed from the date of liver resection until death, liver transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
11
0
5
Order By: Relevance
“…The AFP value did not predict overall survival either. Prognostic factors assessing liver functional capacity or the intensity of subclinical inflammation may also predict the prognosis of HCC patients [ 40 , 41 , 42 , 43 , 44 ]. In our cohort of patients, ALBI grade predicted overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The AFP value did not predict overall survival either. Prognostic factors assessing liver functional capacity or the intensity of subclinical inflammation may also predict the prognosis of HCC patients [ 40 , 41 , 42 , 43 , 44 ]. In our cohort of patients, ALBI grade predicted overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted by Zhang et al [5] showed that the ALBI grade was a good predictor of overall survival in BCLC stage 0/A patients but not in other BCLC stages. Thus, it is possible to conclude that the novel ALBI score is certainly one of the most validated scores for predicting PHLF, as described in Table 1 [5,33,45,[37][38][39][40][41][42][43][44] .…”
Section: Albi Scorementioning
confidence: 97%
“…These models were gradually adopted to predict PHLF and exhibited a certain predictive ability [13][14][15][16]. Recently, ALBI and PALBI model were developed to evaluate liver function and used to predict PHLF after hepatectomy for HCC [17][18][19][20][21][22][23]. Although various studies demonstrated the usefulness of these liver functional reserve models in prediction of PHLF, few studies compared their accuracy in HCC patients undergoing major hepatectomy.…”
Section: Ivyspring International Publishermentioning
confidence: 99%